La función de juzgar. ¿Y quién juzga a quien juzga (...) y a quien juzga (...) y a quien juzga (...)? - Morales Bermúdez Escomel, Ignacio (2020)
This paper seeks to address an always difficult issue such as that of the work of the judge in the Law. It is difficult to determine a form of qualification capable of indicating when a legal decision is appropriate or not. One could carry out this qualification by betting on ideals linked to the work of the judge; In this sense, we could say that it applies previously established norms without ruling out the possibility of generating interpretations of them that contribute to creating new criteria or new rules favorable to society. Likewise, we could say that this function must be exercised with autonomy and freedom, in order to ensure that decisions are not influenced by the interests of third parties. If he did not do it that way, then his work would be flawed. In this sense, it is the object of the present work to ask if it is possible that the judge is provided with mechanisms that allow him to maintain a coherent and predictable action, in order to generate legal certainty.